Femtosecond photoexcitation dynamics inside a quantum solvent - Bernhard Thaler (Nature Portfolio, 2018)
Femtosecond laser spectroscopy has contributed to our understanding of structure and function of matter. Here, the authors explore the applicability of superfluid helium nanodroplets as a sample preparation method that allows investigation of previously inaccessible classes of tailor-made or fragile molecular systems.